Optimized multiple output high current switch-mode power supply for mobile robot applications - Castillo, Gaudan Albert Chekov L. (2009)
A mobile robot is an electronic application that integrates multiple systems. Thus, a mobile robot requires a power supply that can provide power at different voltages. In addition, the power supply should have a small form factor to save space and a high power density to power loads with high current ratings such as DC motors. Efficiency is also vital for longer mobile robot operation All these requirements can be satisfied through the use of switching power supplies. An optimized multiple output high current power supply is presented to be used for mobile robot applications. The power supply will provide standard voltage levels required by standard ICs and logic circuits. A high-power output will be available for high-current loads. A multiple output flyback will be used to output the low-power standard level voltages. A buck converter will be implemented to provide the high-current output for motor loads. Control will be performed by a standard PWM IC. The multiple output converter will be powered by a 24 volt lead-acid battery.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Mobile robots; Switching power supplies; Power electronics; Switch-mode power supply